Effect of Pressure Support vs T-Piece Ventilation Strategies During Spontaneous Breathing Trials on Successful Extubation Among Patients Receiving Mechanical Ventilation: A Randomized Clinical Trial - Subirà, Carles (JAMA, 2019)
IMPORTANCE: Daily spontaneous breathing trials (SBTs) are the best approach to determine whether patients are ready for disconnection from mechanical ventilation, but mode and duration of SBT remain controversial. OBJECTIVE: To evaluate the effect of an SBT consisting of 30 minutes of pressure support ventilation (an approach that is less demanding for patients) vs an SBT consisting of 2 hours of T-piece ventilation (an approach that is more demanding for patients) on rates of successful extubation. DESIGN, SETTING, AND PARTICIPANTS: Randomized clinical trial conducted from January 2016 to April 2017 among 1153 adults deemed ready for weaning after at least 24 hours of mechanical ventilation at 18 intensive care units in Spain. Follow-up ended in July 2017. INTERVENTIONS: Patients were randomized to undergo a 2-hour T-piece SBT (n = 578) or a 30-minute SBT with 8-cm H(2)O pressure support ventilation (n = 557). MAIN OUTCOME AND MEASURES: The primary outcome was successful extubation (remaining free of mechanical ventilation 72 hours after first SBT). Secondary outcomes were reintubation among patients extubated after SBT; intensive care unit and hospital lengths of stay; and hospital and 90-day mortality. RESULTS: Among 1153 patients who were randomized (mean age, 62.2 [SD, 15.7] years; 428 [37.1%] women), 1018 (88.3%) completed the trial. Successful extubation occurred in 473 patients (82.3%) in the pressure support ventilation group and 428 patients (74.0%) in the T-piece group (difference, 8.2%; 95% CI, 3.4%-13.0%; P = .001). Among secondary outcomes, for the pressure support ventilation group vs the T-piece group, respectively, reintubation was 11.1% vs 11.9% (difference, −0.8%; 95% CI, −4.8% to 3.1%; P = .63), median intensive care unit length of stay was 9 days vs 10 days (mean difference, −0.3 days; 95% CI, −1.7 to 1.1 days; P = .69), median hospital length of stay was 24 days vs 24 days (mean difference, 1.3 days; 95% CI, −2.2 to 4.9 days; P = .45), hospital mortality was 10.4% vs 14.9% (difference, −4.4%; 95% CI, −8.3% to −0.6%; P = .02), and 90-day mortality was 13.2% vs 17.3% (difference, −4.1% [95% CI, −8.2% to 0.01%; P = .04]; hazard ratio, 0.74 [95% CI, 0.55-0.99]). CONCLUSIONS AND RELEVANCE: Among patients receiving mechanical ventilation, a spontaneous breathing trial consisting of 30 minutes of pressure support ventilation, compared with 2 hours of T-piece ventilation, led to significantly higher rates of successful extubation. These findings support the use of a shorter, less demanding ventilation strategy for spontaneous breathing trials. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT02620358